2020
DOI: 10.14309/ctg.0000000000000116
|View full text |Cite|
|
Sign up to set email alerts
|

Reduced Lysosomal Acid Lipase Activity in Blood and Platelets Is Associated With Nonalcoholic Fatty Liver Disease

Abstract: OBJECTIVES: To investigate whether blood total lysosomal acid lipase activity (BT-LAL) levels are uniquely associated with the noncirrhotic and cirrhotic stages of nonalcoholic fatty liver disease (NAFLD) and with protection from NAFLD in metabolically/genetically predisposed subjects and a normal liver. To clarify which enzyme-carrying circulating cells are involved in reduced BT-LAL of NAFLD. METHODS: In a cross-sectional study, BT-LAL was measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
0
12
0
1
Order By: Relevance
“…Several studies have demonstrated reduced circulating LAL activity in patients with nonalcoholic fatty liver disease (NAFLD) [ 59 , 60 ]. Since we have observed inhibition of L2 on neutral lipases as low as 1 μM, this concentration of the inhibitor may also not be useful to study the role of LAL in diseases, including NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated reduced circulating LAL activity in patients with nonalcoholic fatty liver disease (NAFLD) [ 59 , 60 ]. Since we have observed inhibition of L2 on neutral lipases as low as 1 μM, this concentration of the inhibitor may also not be useful to study the role of LAL in diseases, including NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Lower LAL activity in NASH is associated with increased necroinflammation and NASH severity ( Vespasiani-Gentilucci et al, 2017 ). Some studies did not detect differences in earlier stages of NAFLD, but LAL by DBS was found to be reduced in cirrhosis of both cryptogenic ( Vespasiani-Gentilucci et al, 2016 ; Gravito-Soares et al, 2019 ) and known etiologies ( Vespasiani-Gentilucci et al, 2016 ; Ferri et al, 2020 ). Gravito-Soares et al showed that LAL activity can be used to predict cryptogenic cirrhosis and fibrosis more effectively than existing markers ( Gravito-Soares et al, 2019 ).…”
Section: The Role Of Lal In Fatty Liver Diseasementioning
confidence: 97%
“…In agreement with this, Gomaraschi et al report that low LAL activity in liver biopsies of NAFLD patients was shown to be independent of LAL expression ( Gomaraschi et al, 2019 ). Other etiologies of fatty liver disease also exhibit lowered LAL activity, including alcoholic and HCV-related liver disease, though NAFLD shows a greater reduction of LAL ( Angelico et al, 2017 ; Tovoli et al, 2017 ; Ferri et al, 2020 ). This suggests that lowered LAL activity is partly secondary to liver disease, since various etiologies share the same characteristic of low LAL, but the even lower LAL in NAFLD specifically suggests that the metabolic abnormalities associated with NAFLD may also be related to LAL activity directly ( Baratta et al, 2015b ; Angelico et al, 2017 ).…”
Section: The Role Of Lal In Fatty Liver Diseasementioning
confidence: 99%
“…So far, many cell types have been investigated for their contribution to the pathogenesis of nonalcoholic fatty liver disease and its more severe inflammatory form, NASH. The role of platelets 6 , monocytes/macrophages, hepatocytes, hepatic stellate cells, endothelial cells, neutrophils, T lymphocytes, natural killer cells and other innate lymphoid cells has been extensively studied 7,8 . However, research on the role of erythrocytes has remained scarce.…”
Section: Introductionmentioning
confidence: 99%